THE VOICE OF E-LEARNERS - D´Angelo, Eugenio; Formica, Costantino; Dimopoulou, Nefeli; Kazantzidou, Natassa; Protopsaltis, Aristidis; Schorer, Antonia; Gavalas, Damianos; Kostas, Apostolos; Makrides, Gregoris; Kyrillou, Roula; Capablanca Francés, Lucía; Belda Anaya, Raquel (16th International Technology, Education and Development Conference, 2022)
In recent years, online learning has experienced a remarkable demand from students who want to complete their training and improve their professional skills and job position, being able to adapt this training to their pace of life. The pandemic situation due to Covid has made this increase more evident and the platforms that offer MOOCs and online training have seen a striking increase in enrolment in their courses. Due this high demand for courses online, it is necessary to evaluate whether this training is fulfilling its purpose. The main objective of any quality management system is customer satisfaction. In order to determine the degree of satisfaction, an appropriate measurement system is required to obtain qualitative and quantitative quality information in order to be able to make decisions and establish proposals for improvements aimed at achieving the objective of satisfying the customer, the learner. With the data gathered in the pilot run of the tracking tool developed in the ASTRE project, the voice of the learner has been heard. These data have been analysed and general recommendations for MOOC and e-learning providers have been issued. This important feedback can help to detect improvements and/or establish the strengths of the training offere
Keywords: improve; quality; egressed; tracking; survey